Spectrum of prism graph and relation with network related quantities - Ali Raza; Mobeen Munir; Tasawar Abbas; Sayed M Eldin; Ilyas Khan (AIMS Mathematics, 2023)
Spectra of network related graphs have numerous applications in computer sciences, electrical networks and complex networks to explore structural characterization like stability and strength of these different real-world networks. In present article, our consideration is to compute spectrum based results of generalized prism graph which is well-known planar and polyhedral graph family belongs to the generalized Petersen graphs. Then obtained results are applied to compute some network related quantities like global mean-first passage time, average path length, number of spanning trees, graph energies and spectral radius.